Modernism in European Drama: Ibsen, Strindberg, Pirandello, Beckett : Essays from Modern Drama - Innes, Christopher, 1941-; Marker, Frederick J. (Book collections on Project MUSE., 1998)
"This collection of essays, drawn from scholarship over the last forty years, explores the drama of four of the most influential proponents of modernism in European drama: Ibsen, Strindberg, Pirandello, and Beckett. Although there are other dramatists who also contributed to Modernism, these four illustrate widely different and contrasting aspects of the movement. Since discussions of Modernism are generally restricted to poetry, novels, or the fine arts (painting, sculpture), examining theatre from this perspective covers new ground."--Jacket.